Coronatine Modulated the Generation of Reactive Oxygen Species for Regulating the Water Loss Rate in the Detaching Maize Seedlings - Haiyue Yu (Agriculture, 2021)
Coronatine (COR), a structural and functional mimic of jasmonates, is involved in a wide array of effects on plant development and defense response. The present study aims to investigate the role of COR, in counteracting drought stress by modulating reactive oxygen species (ROS) homeostasis, water balance, and antioxidant regulation in detached maize plants. Our results showed that COR can markedly decrease the water loss rate, but the antioxidants diphenyleneiodonium chloride (DPI) and dimethylthiourea (DMTU) eliminate the effect of water loss induced by COR. Using the dye 2′,7′-dichlorofluorescein diacetate (H2DCF-DA) loaded in the maize epidermis guard cells, it is observed that COR could increase ROS production, and then antioxidants DPI and DMTU decreased ROS production induced by COR. In addition, the expression of ZmRBOHs genes, which were associated with ROS generation was increased by COR in levels and ZmRBOHC was highly expressed in the epidermis guard cells. Moreover, COR-treated plants increased H2O2 and O2−· accumulation, antioxidant enzyme activities in control plants, while COR relieved the ROS accumulation and antioxidant enzyme activities under PEG treatment. These results indicated that COR could improve maize performance under drought stress by modulating ROS homeostasis to maintain water loss rate and antioxidant enzyme activities.